Exploring the longitudinal expression dynamics of midguts in adult female Amblyomma americanum ticks - Stephen Lu; Lucas C. de Sousa-Paula; Jose M. C. Ribeiro; Lucas Tirloni (BMC Genomics)
Abstract Background Female ticks remain attached to their host for multiple days to complete a blood meal. This prolonged feeding period is accompanied by a significant increase in the tick’s size and body weight, paralleled by noteworthy changes to the tick midgut. While the midgut is recognized for its established role in blood storage and processing, its importance extends to playing a crucial role in the acquisition, survival, and proliferation of pathogens. Despite this, our overall understanding of tick midgut biology is limited. Results Our transcriptome analysis identified 15,599 putative DNA coding sequences (CDS), which were classified into 26 functional groups. Dimensional and differential expression analyses revealed four primary transcriptional profiles corresponding to unfed, slow-feeding, transitory (from slow- to rapid-feeding), and rapid-feeding stages. Additionally, comparing the current dataset with previously deposited transcriptome from other tick species allowed the identification of commonly expressed transcripts across different feeding stages. Conclusion Our findings provide a detailed temporal resolution of numerous metabolic pathways in the midgut of A. americanum adult females throughout the feeding process, highlighting the dynamic transcriptional regulation of the tick’s midgut as feeding progresses. Furthermore, we identified conserved transcripts across three different tick species that exhibit similar expression patterns. This knowledge not only enhances our understanding of the physiological processes within the tick midgut but also opens up potential avenues for developing control methods that target multiple tick species.